The Role of Environmental Factors in the Incidence of Tuberculosis and Stunting in Children - Indayah Dewi Tunggal; Ayun Sriatmi; Martini Martini (GLOBAL HEALTH SCIENCE GROUP, 2025)
Environmental factors play a crucial role in the incidence of tuberculosis (TB) and stunting in children. This study highlights the significant impact of environmental conditions, such as poor ventilation and inadequate sanitation, on the increased risk of both stunting and TB. Poor ventilation, uncontrolled humidity, and high occupancy density are directly linked to higher TB incidence, while inadequate sanitation has been shown to negatively affect child growth and increase the risk of stunting. Recent data indicates that children living in poor sanitation conditions are twice as likely to experience stunting, while those in poorly ventilated environments are at higher risk of contracting TB. To reduce the burden of both health issues, it is recommended to improve household ventilation, enhance sanitation conditions, and provide community-based health education. These interventions can help lower the prevalence of TB and stunting in children, particularly in resource-limited areas.